Heterogeneous treatment effects of integrated soil fertility management on crop productivity: Evidence from Nigeria - Kato, Edward; Nkonya, Ephraim M.; Place, Frank (International Food Policy Research Institute, 2011)
This study compares the impacts of integrated soil fertility management (ISFM) on crop production with use of either mineral fertilizer or organic manure alone. We also investigate the conditions under which .ISFM technology has greater beneficial effects on yields and the factors constraining its uptake. To answer these questions, the study uses a cross-sectional, plot-level data set collected in Nigeria by the International Food Policy Research Institute and the World Bank in 2009. Using both quasi experimental matching estimators and multivariate regression approaches, it finds that overall ISFM has robustly significant positive effects on crop production. The study also finds that ISFM positively affects crop production on plots with customary tenure, sandy soils, and clay soils—conditions that are normally perceived to be less favorable for crop production. The results also show ISFM to be more effective on plots with mild erosion or no erosion. On the constraints, we find that households with limited livestock, equipment, labor, and land are less likely to use ISFM technology, and the extension services currently do not seem to be disseminating ISFM. This evidence provides strong support for efforts to promote ISFM in Nigeria and in other regions with comparable conditions, but adequate attention must be paid to the biophysical conditions of the plots and the household's access to labor endowments, livestock, equipment, and tenure conditions if this technology is to be scaled up and more widely used in Sub-Saharan Africa.